Efektivitas Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) Kota Cimahi dalam Pencegahan Kekerasan dalam Rumah Tangga - Amanda Al-Yaasiin Al-Yaasiin; Teguh Yuwono (Journal of Politic and Government Studies, 2026)
The Integrated Service Center for the Protection of Women and Children (P2TP2A) of Cimahi City was established to address issues of violence against women and children, including domestic violence involving family members. This institution aims to raise awareness and enhance public understanding of these issues. This study focuses on examining the effectiveness of P2TP2A Cimahi City in preventing domestic violence. The research was conducted in Cimahi City, West Java, using in-depth interviews and observation as data collection techniques. In its implementation, the researcher found that P2TP2A Cimahi City has undertaken various efforts to prevent domestic violence, which indicate its level of effectiveness in prevention activities. However, in achieving optimal effectiveness, several challenges were identified. These include a shortage of personnel resulting in multiple workloads, inadequate facilities and infrastructure, and challenges originating from community attitudes. Therefore, this study recommends the establishment of clearer regulations regarding the distribution of workloads among staff members in order to improve the overall performance and effectiveness of P2TP2A.